Effects of sudden change in pitch angle on oscillating wind turbine airfoil performances. (August 2017) - Oueslati, M.M.; Dahmouni, A.W.; Nasrallah, S. Ben
Abstract: In this paper, the aerodynamic performances of a wind turbine airfoil in sinusoidal pitching motion was numerically predicted and analyzed using the two-dimensional singularity method. A parametric study based on the sudden pitch angle rate variation, the reduced frequency and the pitching amplitudes have been investigated. The results highlight the sudden change effect in pitch angle on the aerodynamic performances of the airfoil and the shedding wake. The aspect of lift and drag coefficient loops and hysteresis were customized regarding to the pure sinusoidal motion case. The dynamic stall phenomenon, which occurs during the rapid change in pitch angle, produces more drag forces influencing the wind turbines performance.